2018
DOI: 10.1111/gfs.12391
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolizidine alkaloid production of Jacobaea aquatica and contamination of forage in meadows of Northern Austria

Abstract: Jacobaea aquatica (=Senecio aquaticus, Asteraceae), marsh ragwort, grows regionally in low management intensity wet grasslands in various European countries. The plant can be regarded as a noxious weed as it contains pyrrolizidine alkaloids (PAs), which cause health problems in livestock. In the Waldviertel region of Northern Austria, marsh ragwort has established dense populations as the fertilizing and production intensity of the meadows changed during the last decades. Ragwort biomass production and alkaloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
3
0
4
Order By: Relevance
“…In particular, it has recently been observed that some species like S. jacobaea (syn. : Jacobaea vulgaris), Senecio aquaticus [38,39], or Senecio inaequidens (a neophyte to European areas) [40], may mass-infest pasture areas or public land (parks, greenery, nature preserves, and ancillary areas of transport routes/roadsides) [41]. Those cuttings and green wastes naturally contain a high load of toxic PAs and if used as organic fertilizers in non-PA-crops, these PAs could potentially be passed on via horizontal PA-transfer.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it has recently been observed that some species like S. jacobaea (syn. : Jacobaea vulgaris), Senecio aquaticus [38,39], or Senecio inaequidens (a neophyte to European areas) [40], may mass-infest pasture areas or public land (parks, greenery, nature preserves, and ancillary areas of transport routes/roadsides) [41]. Those cuttings and green wastes naturally contain a high load of toxic PAs and if used as organic fertilizers in non-PA-crops, these PAs could potentially be passed on via horizontal PA-transfer.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in areas with marsh ragwort a total PA content of 100 mg/kg is easily reached in forage cut in summer, which provides more than 1-3 mg PAs/kg body weight per day to horses (Chizzola et al 2019). This massively exceeds the recommended oral intake limit of 1 µg PA/kg bodyweight/ day.…”
Section: Pa Contamination Of Equine Supplements Put Into Perspectivementioning
confidence: 99%
“…Another important fact is, that the diet of horses mostly consists of forage, which, depending on the geographical location, the harvest date and the year, can be massively contaminated by ragwort (Jacobaea vulgaris, Senecio jacobaea) or marsh ragwort (Jacobaea aquatica) (Chizzola et al 2019).…”
Section: Pa Contamination Of Equine Supplements Put Into Perspectivementioning
confidence: 99%
“…Bei Heu hängt die Verunreinigung mit Kreuzkrautarten ( Senecio jacobaea, Jacobaea aquatica ) stark von der geografischen Lage und dem Erntezeitpunkt ab. Aber auch die klimatischen Bedingungen des jeweiligen Jahres spielen eine wichtige Rolle 9 .…”
Section: Vertreter Und Toxizitätunclassified
“…Auch Verunreinigungen von Futter mit PA können für die Gesundheit von Pferden gefährlich werden. Dies betrifft sowohl Raufutter als auch Kraftfutter (wie Hafer oder kommerzielle Futtermischungen) und vermutlich auch Zusatzfuttermittel sowie Nutraceuticals 7 , 9 , 10 . Auch bei geringer täglicher PA-Belastung, aber langfristiger Verabreichung eines PA-belasteten Futtermittels, ist es aufgrund der kumulativen Schäden denkbar, dass sich dies für Pferde nachteilig auswirkt.…”
Section: Introductionunclassified